Guidelines for inflammation models in mice for food components. Issue 3 (4th July 2022) - Han, Yanhui; Itenberg, Sasha A.; Wu, Xian; Xiao, Hang
Abstract: Inflammation is one of the major health threats to humans, and it is associated with various chronic diseases, including metabolic syndrome, type 2 diabetes, cardiovascular diseases, and several types of cancer. For example, colonic inflammation can result in the damage of the intestinal barrier, as indicated by invasion of immune cells and reduced tight junctions. Inflammatory responses can also lead to erythema and edema on skin. The intervention of dietary components offers striking possibilities for the prevention of inflammation by modulating the inflammatory signaling pathways and microbiota–inflammation axis. Thus, the preclinical animal models are of critical importance for investigating the anti‐inflammatory effects of food components. This guideline introduces two inflammatory mouse models: dextran sulfate sodium‐induced colonic inflammation and 12‐ O ‐tetradecanoylphorbol‐13‐acetate‐induced skin inflammation. These mimic models offer the potential to assess food components in attenuating the colonic and skin inflammation in humans. Abstract : Dietary intervention of various foods shows potential benefits against inflammation. The preclinical animal models are of critical importance for investigating the anti‐inflammatory effects of food components. This guideline introduces two inflammatory mouse models: dextran sulfate sodium (DSS)‐induced colonic inflammation and 12‐ O ‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced skin inflammation